Horrid Henry rocks - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 2016)
Collects four stories recounting the adventures of Horrid Henry as he torments his younger brother, ruins Moody Margaret's sleepover, irritates his teacher, and tries to trick his family into seeing his favorite band.
-
"Four laugh-out-loud stories!"--Cover.
English language and literature.
Keywords: Rock music -- Juvenile fiction; Short stories; Human behavior -- Juvenile fiction; Behavior -- Fiction; Rock music -- Fiction; Short stories; Human behavior -- Fiction; Rock music -- Fiction; Short stories